Pharmaceutical and therapeutic interventions for anxiety in terminal illness. (2nd March 2022) - Williams, Chloe; Dippenaar, Enrico
Abstract : Background: Anxiety is a sensation where the human body reacts to a range of emotions in an adverse way, leading to symptoms of nervousness, anxiousness and excessive fear. Anxiety disorders arise in patients who are receiving end-of-life care for multiple reasons, including confronting mortality and having to accept a change in lifestyle. Therefore, a vital part of managing the symptoms of patients who are terminally ill is ensuring they receive the most appropriate intervention for these disorders, whether that be pharmaceutical or a non-pharmaceutical therapy. Methods: A rapid literature search was conducted between 20 February 2021 and 3 March 2021 through two main online databases (CINAHL Plus and PsycInfo). A total of 848 entries matched the search criteria and, after screening, seven papers were collated and used within this review. Results: All pharmacological interventions were shown to reduce anxiety-related symptoms in patients receiving end-of-life care. Most non-pharmaceutical therapeutic interventions showed some effects, including significant reductions in symptoms when evaluated against the Hospital Anxiety and Depression Scale or individual disclosure of improvements in quality of life. Conclusions: While none of the studies in this review directly compared pharmacological with non-pharmacological therapeutic interventions, both can improve end-of-life care for terminally ill patients. When treating patients diagnosed with a terminal illness who are receiving palliative care, their prognosis, time frame and personal wishes are key aspects to consider when deciding on the most appropriate management strategy for anxiety disorders.